2020
DOI: 10.1049/gtd2.12090
|View full text |Cite
|
Sign up to set email alerts
|

Optimization to POD parameters of DFIGs based on the 2nd order eigenvalue sensitivity of power systems

Abstract: Here, the analytical model of the 2nd order eigenvalue sensitivity is improved, and applied to optimize the parameters of the power oscillation dampers of the doubly‐fed induction generators. To solve the 2nd order eigenvalue sensitivity, the eigenvector sensitivity is required whose difficulty lies in insufficient constraints, for which two constraints about the magnitude and the angle of eigenvector elements are newly introduced, and the normalization conditions are derived to solve the eigenvector sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…The control parameters are gradually changed to draw the locus of the LFO modes to verify the control effect. It is computationally expensive since each time only one parameter is checked [26]. Sensitivities of eigenvalues are more effective to decide the control effect [27].…”
Section: Literature Review and Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…The control parameters are gradually changed to draw the locus of the LFO modes to verify the control effect. It is computationally expensive since each time only one parameter is checked [26]. Sensitivities of eigenvalues are more effective to decide the control effect [27].…”
Section: Literature Review and Comparisonmentioning
confidence: 99%
“…Multiplying a complex number k∠θ to both sides of ( 26), one obtains (28). It can be found that the eigenvectors corresponding to different k and θ satisfy (26). Hence, for each eigenvalue, there are numerous eigenvectors, as shown in Figure 5.…”
Section: The First-and Second-order Eigen-sensitivitiesmentioning
confidence: 99%